Anomalous compliance and early yielding of nanoporous gold. (July 2015) - Ngô, Bao-Nam Dinh; Stukowski, Alexander; Mameka, Nadiia; Markmann, Jürgen; Albe, Karsten; Weissmüller, Jörg
Abstract: We present a study of the elastic and plastic behavior of nanoporous gold in compression, focusing on molecular dynamics simulation and inspecting experimental data for verification. Both approaches agree on an anomalously high elastic compliance in the early stages of deformation, along with a quasi immediate onset of plastic yielding even at the smallest load. Already before the first loading, the material undergoes spontaneous plastic deformation under the action of the capillary forces, requiring no external load. Plastic deformation under compressive load is accompanied by dislocation storage and dislocation interaction, along with strong strain hardening. Dislocation-starvation scenarios are not supported by our results. The stiffness increases during deformation, but never approaches the prediction by the relevant Gibson–Ashby scaling law. Microstructural disorder affects the plastic deformation behavior and surface excess elasticity might modify elastic response, yet we relate the anomalous compliance and the immediate yield onset to an atomistic origin: the large surface-induced prestress induces elastic shear that brings some regions in the material close to the shear instability of the generalized stacking fault energy curve. These regions are elastically highly compliant and plastically weak.